An Overview of the Mexican Blueberry Industry - Feng Wu; Zhengfei Guan (EDIS)
Blueberries are a healthy source of antioxidants and vitamins. Global demand and production have been increasing rapidly over the last decade. This publication provides an overview of the Mexican blueberry industry in terms of production, price, trade, and cultural practices. It also sheds light on factors that have contributed to the fast growth of the blueberry industry in Mexico.